Debt Relief and Incentive-Compatible Conditionality - Almuth Scholl (Verein für Socialpolitik, 2010)
This paper analyzes the effectiveness of debt relief and foreign aid in a neoclassical growth framework with a conflict of interest between the donor and the recipient government. Conditionality is modeled as a dynamic contract that is enforceable only by the threat of aid sanctions. Quantitative results show that debt relief and unconditional foreign aid have no long-run effects since the recipient government accumulates new loans. In contrast, debt relief in combination with conditional foreign aid is effective in promoting growth and reducing poverty. However, debt relief may be counter-productive since they make the punishment threat less severe such that self-enforcing aid contracts are characterized by weak conditionality.
Keywords: F35; O11; O19; 330; debt relief; foreign aid; conditionality; limited enforceability; dynamic contracts; neoclassical growth